Pengaruh Harga Minyak Mentah Dunia dan Cadangan Minyak Mentah Indonesia terhadap Volume Ekspor Minyak Mentah Indonesia 1996-2024 - Sulthan Awwal Fakhruddin; Harya Kuncara Wiralaga; Dicky Iranto (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the influence of world crude oil prices and Indonesia's crude oil reserves on the volume of Indonesia's crude oil exports for the period 1996-2024. The global crude oil market has experienced significant fluctuations due to various factors such as geopolitical conflicts, the COVID-19 pandemic, and the shift towards renewable energy. Indonesia, as a country that has transitioned from a net exporter to a net importer of crude oil, faces challenges in maintaining its export volume amidst declining domestic production and increasing energy consumption. This research employs a quantitative approach with a time series analysis method using secondary data obtained from the Central Bureau of Statistics (BPS) and the Energy Institute. The analytical method used is the Error Correction Model (ECM) to examine both short-term and long-term relationships between variables. The results indicate that in the long term, world crude oil prices have a negative and significant effect, while Indonesia's crude oil reserves have a positive and significant effect on the volume of crude oil exports. In the short term, world crude oil prices do not have a significant effect, whereas crude oil reserves continue to have a positive and significant effect. The coefficient of determination (Adjusted R²) in the long-term model reaches 92.48%, indicating that both independent variables are able to explain most of the variation in Indonesia's crude oil export volume. These findings provide important implications for the government in formulating energy policies, maintaining national energy security, and encouraging exploration of new crude oil reserves to support sustainable export activities.